Prevalence and associated factors of metabolic syndrome and its individual components among adolescents - Getabalew Endazenaw Bekel; Gloria Thupayagale-Tshweneagae (International Journal of Public Health Science (IJPHS), 2020)
Metabolic syndrome is a growing health problem that affects the whole population including adolescents due to change in lifestyles. It is strongly associated with different lifestyle behavioral factors. The objective of the study was to investigate the magnitude and associated factors of metabolic syndrome in adolescents. School based cross-sectional study design was used. The sample size for this study was 844 and 8 high schools were randomly selected from Addis Ababa city Administration. Simple random sampling technique was used to select each participant. Data was analyzed using SPSS version 24 and descriptive summary statistics produced to present the findings. In this study among the components of metabolic syndrome, the highest prevalence was observed in high level of fasting blood glucose level 57.8%, followed by high waist circumference 32.2%. The overall prevalence of metabolic syndrome from the total study participants was 12.4%. Smoking, alcohol intake, performing vigorous or modern physical activity, body mass index and time spent for sedentary activities were factors which had significant association with individual metabolic abnormalities. In conclusions the magnitude of metabolic syndrome is common problem of adolescents in the study area.